Climate Change Adaptation Strategies: A Review of African and USA Policies - Omodolapo Eunice Ogunsola, (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
This Review provides a concise overview of the comprehensive review analyzing the climate change adaptation policies implemented in Africa and the United States. As these regions grapple with the intricate challenges posed by climate change, understanding the nuances of their respective strategies is imperative for developing effective and context-specific solutions. In Africa, characterized by ecological diversity and vulnerability, adaptation policies are explored against the backdrop of resource constraints. The review delves into collaborative efforts, such as the COVAX initiative, to ensure equitable access to climate adaptation resources. Logistical hurdles, innovative solutions, and community-based approaches are scrutinized as Africa navigates the complexities of adapting to changing precipitation patterns, extreme weather events, and threats to food security. In contrast, the United States, with its varied climate and developed infrastructure, faces a different set of challenges. The review examines the multifaceted policies implemented across federal, state, and local levels, emphasizing the integration of climate considerations into infrastructure planning. The role of technological innovations and sustainable practices is explored in the context of addressing the impacts of climate change, including sea-level rise, wildfires, and shifting precipitation patterns. The Review highlights the significance of equitable and inclusive adaptation policies, ensuring that vulnerable populations in both Africa and the USA are adequately protected. It synthesizes key findings regarding the strengths and limitations of current policies, providing a foundation for understanding the effectiveness of climate change adaptation strategies. As climate change continues to reshape global landscapes, this comparative review contributes to the ongoing discourse on policy innovation, cross-national cooperation, and the imperative to build resilient societies capable of navigating an uncertain climatic future.
Keywords: Climate Change; Policies; Adaption; Strategies; Infrastructures